Automated Testing of Environment-Dependent Programs - A Case Study of Modeling the File System for Pex - Kong, Soonho; Tillmann, Nikolai; Halleux, Jonathan "Peli" de (Proc. 6th International Conference on Information Technology: New Generations (ITNG'09), 2009)
Programs that interact with the file system are a classical challenge for automated software testing. A common approach to handling this problem is to insert an abstraction layer between the application and the file system. However, even with a well-defined abstraction layer, the burden on the software developer or tester is still high: they have to understand the subtleties of the file system to craft a meaningful set of test cases. The file system is accessed through a complex API, which often causes developers to overlook obscure yet possible corner cases. In this paper, we present a parameterized model of the file system that can be used in conjunction with Pex, an automated test generation tool, to test code that depends on the file system.